Continuing Professional Development: Examining the Basics - KIRWAN, GLORIA (My University, 2012)
Drawing on data collected as part of a national study of social work and continuing professional development (CPD) in Ireland which was carried out by the author between 2005 and 2007 (Kirwan, 2010), this article pinpoints issues related to CPD that are working well in the Irish context but also throws a spotlight on issues which serve to discourage and prevent social workers from engaging in CPD activities. In light of the inhibitors experienced by social workers in accessing CPD, this article also flags in a critical way, some of the assumptions that are often unquestioningly attached to its promotion as a yardstick of quality assurance. The possibility that differences may exist between individual CPD needs versus corporate or agency-led CPD needs is raised here as an issue which the profession will need to consider in the context of the introduction of professional registration. The article concludes by posing questions for the social work profession in Ireland about its future engagement in CPD and what outcomes can be used to measure its usefulness and effectiveness as a means of raising practice standards.
PUBLISHED
Keywords: CPD; Continuing professional development